2004
DOI: 10.1111/j.1524-4725.2004.30151.x
|View full text |Cite
|
Sign up to set email alerts
|

In-Transit Metastasis From Primary Cutaneous Squamous Cell Carcinoma in Organ Transplant Recipients and Nonimmunosuppressed Patients: Clinical Characteristics, Management, and Outcome in a Series of 21 Patients

Abstract: In-transit metastasis from cutaneous SCC is a unique presentation of metastatic SCC, more commonly described in organ transplant recipients, and is associated with poor prognosis in that group. This description represents the largest experience with in-transit metastases from cutaneous SCC in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
126
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(128 citation statements)
references
References 17 publications
2
126
0
Order By: Relevance
“…Many of the immunosuppressive agents used in OTRs to prevent organ rejection have direct or indirect suppression of T-cell function. 7 Carucci et al 8 suggested that in-transit metastases tend to occur after high-risk SCC more frequently in OTRs than in patients who have not received transplants. They also noted that these in-transit metastases tended to occur after high-risk tumors of the forehead or scalp and were associated with a poor prognosis in OTRs.…”
Section: T H E R E a R E M O R E T H A Nmentioning
confidence: 99%
“…Many of the immunosuppressive agents used in OTRs to prevent organ rejection have direct or indirect suppression of T-cell function. 7 Carucci et al 8 suggested that in-transit metastases tend to occur after high-risk SCC more frequently in OTRs than in patients who have not received transplants. They also noted that these in-transit metastases tended to occur after high-risk tumors of the forehead or scalp and were associated with a poor prognosis in OTRs.…”
Section: T H E R E a R E M O R E T H A Nmentioning
confidence: 99%
“…50 Most (15 of 22) of the primary tumors were located on the head and face; although, in 3 of 22 subjects, the primary tumor site could not be determined. 50 In-transit metastases were discovered an average of 10 weeks after treatment of the primary tumor. 50 Intransit metastases were more common in OTR and associated with increased morbidity and mortality.…”
Section: In-transit Metastasismentioning
confidence: 90%
“…50 In that study, the in-transit metastases tended to be less than 8.0 mm in size with mean distance of 2.5 cm from the primary tumor. 50 Most (15 of 22) of the primary tumors were located on the head and face; although, in 3 of 22 subjects, the primary tumor site could not be determined. 50 In-transit metastases were discovered an average of 10 weeks after treatment of the primary tumor.…”
Section: In-transit Metastasismentioning
confidence: 95%
See 2 more Smart Citations